Soziale Elite und Christentum Studien zu ordo-Angehörigen unter den frühen Christen - Weiß, Alexander; Weiß, Alexander 1968- (Berlin/Boston De Gruyter, 2015)
The notion that early Christianity was a 'lower class religion' is surely outdated. Yet the extent to which members of the social elites turned to the new faith remains a matter of intense scholarly dispute. Many researchers argued against the idea that the social elites were already represented among early Christians. However, the sources give extensive evidence that senators and local officials were among the Christians of the 1stcentury CE. Alexander Weiß, Universität Leipzig.
The notion that early Christianity was a "lower class religion" is surely outdated. Yet the extent to which members of the social elites turned to the new faith remains a matter of intense scholarly dispute. Many researchers argued against the idea that the social elites were already represented among early Christians. However, the sources give extensive evidence that senators and local officials were among the Christians of the 1st century CE
6.4 Übernahme von (lokalen) Ämtern verboten?6.5 Soziale Konventionen als Hindernis; 6.6 Fazit; 7 Christliche ordo-Angehörige im 2., 3. und frühen 4. Jahrhundert; 7.1Christen im ordo senatorius; 7.2 Christen im ordo equester; 7.3 Christen unter den Dekurionen; 8 Resümee und sozialhistorische Konsequenzen; Literaturverzeichnis; Stellenregister; Ortsnamen-, Personen- und Sachregister
Description based upon print version of record
Keywords: Christianity and other religions; Church history -- Primitive and early church, ca. 30-600; Identification (religion); Religions -- Relations; Electronic books; Electronic books; Hochschulschrift